2010
DOI: 10.1021/ac101319k
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Au Nanoparticle Dendrimer-Based Surface Plasmon Resonance Biosensor and Its Application for Improved Insulin Detection

Abstract: Bifunctional hydroxyl/thiol-functionalized fourth-generation polyamidoamine dendrimer (G4-PAMAM)-encapsulated Au nanoparticle (NP) was synthesized and immobilized on a mixed self-assembled monolayer (SAM)-modified gold surface. This modified surface was resistant to nonspecific adsorption of proteins having a wide range of molecular weight and isoelectric points. Part of the dendrimer thiol groups were converted to hydrazide functionalities providing an activated surface available to subsequently immobilize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 73 publications
1
79
0
Order By: Relevance
“…An enhance sensitivity with detection limit of 0.5 pM and EPJ Web of Conferences 162, 01002 (2017) DOI: 10.1051/epjconf/201716201002 InCAPE2017 increased stability were resulted from the GNPsmodified dendrimers. By studying human serum samples with good correlation to standard methods by comparing normal and diabetic patients, the sensor was further certified [60]. An alteration happened due to an increased in surface absorption band to the visible colour change caused by the GNPs aggregation.…”
Section: Applications In Lspr Sensorsmentioning
confidence: 99%
“…An enhance sensitivity with detection limit of 0.5 pM and EPJ Web of Conferences 162, 01002 (2017) DOI: 10.1051/epjconf/201716201002 InCAPE2017 increased stability were resulted from the GNPsmodified dendrimers. By studying human serum samples with good correlation to standard methods by comparing normal and diabetic patients, the sensor was further certified [60]. An alteration happened due to an increased in surface absorption band to the visible colour change caused by the GNPs aggregation.…”
Section: Applications In Lspr Sensorsmentioning
confidence: 99%
“…Many approaches have been explored, such as use of fluorescence, 1 modifying the sensor chip with particles, 2,3 performing a labelled assay using large particles, etc. [4][5][6] Among these, the use of gold nanoparticles (AuNPs) [7][8][9][10][11][12] for signal amplification has obtained significantly improved sensitivity. For example, He et al reported the sandwich approach to detect DNA hybridisation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Corn and coworkers realised 10 fM detection by a combination of poly(A) enzyme chemistry and nanoparticle-amplified SPR imaging. 5 However, the signal enhancement by employing AuNPs can be caused by different factors: [4][5][6][7][8][9][10][11][12] (1) surface mass increase due to AuNPs and more molecules being attached to the AuNPs than the planar gold surface; (2) refractive index change by the particles; (3) electromagnetic field coupling between SPR and localised SPR (LSPR). Among these factors, the coupling effect has been expected to play a dominant role.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The properties of SAMs (i.e., low thickness, densely packed, ordered stacking, high stability, choice of functional heading groups, and resistance against chemicals) 2,4 make these surface coatings suitable for varied applications including control of wetting and adhesion, 5,6 biosensors, 7 microcontact printing, 8 and cell adhesion. 2 Furthermore, these molecular assemblies present interesting structural and physicochemical properties (i.e., small thickness of about 1-3 nm and the molecular size of its structural elements) for radiation-induced nanostructure patterning lithography.…”
Section: Introductionmentioning
confidence: 99%